Covid-19 pandemic impact on colonoscopy service and suggestions for managing recovery - Cadoni, Sergio; Ishaq, Sauid; Hassan, Cesare; Bhandari, Pradeep; Neumann, Helmut; Kuwai, Toshio; Uedo, Noriya; Parra-Blanco, Adolfo; Mulder, Chris J.J.; Binmoeller, Kenneth F.; Leung, Felix W. (Endoscopy International Open, 2020)
Background and aim As the post-peak phase of the epidemic is approaching, there is an urgent need of an action plan to help resume endoscopy activity. To manage the Covid-19 pandemic-imposed backlog of postponed colonoscopy examinations, an efficient approach is needed. The practice of on-demand sedation with benzodiazepines and/or opiates will allow most patients to complete a water-aided examination with minimal or no sedation. Other methods reported to minimize patient discomfort during colonoscopy can be used, in addition to water-aided techniques. Unsedated or minimally sedated patients who do not require recovery or require a shorter one allow rapid turnaround. The practice obviates the need for assistance with deep sedation from anesthesiologists, who may be in short supply. Trainee education in water-aided colonoscopy has been demonstrated to confer benefits. This review provides some insights into the impact of Covid-19 on endoscopy services, challenges ahead, and possible solutions to help recovery of colonoscopy work and training.